Cardioprotective molecule and bioactive compounds of some selected vegetables available in Bangladesh (Journal of the Bangladesh Agricultural University, 2018)
Cardiovascular disease (CVD) is one of the leading causes of death and morbidity as well as imposing a huge economic burden at both country and household level. Upto 90% cardiovascular disease may be preventable if established risk factors are avoided. In this context, dietary nitrate from vegetables was highlighted as a potential candidate for cardio protection. Hence, by supplying dietary nitrate and other bio-active compounds to ease the risk of cardiovascular disease, present research work was carried out. Among the tested vegetables, the highest nitrate content (745 mg/100g) was determined in Indian spinach. In addition, Indian spinach also possesses more chlorophyll (150mg/100g), beta carotene (40mg/100g) and lycopene (34mg/100g) than other tested vegetables in the current study. In case of anti-oxidant content, Indian spinach showed the highest (103mg/100g) vitamin C content. Taken all together, Indian spinach may be a good and cheapest source of cardio protective molecule (nitrate) bioactive compounds to avoid risk of cardiovascular disease.J. Bangladesh Agril. Univ. 16(1): 82-87, April 2018